Contribution of proteomic studies towards understanding plant heavy metal stress response - Hossain, Zahed; Komatsu, Setsuko (Frontiers in Plant Science, 2013)
Modulation of plant proteome composition is an inevitable process to cope with the environmental challenges including heavy metal stress. Soil and water contaminated with hazardous metals not only cause permanent and irreversible health problems, but also result substantial reduction in crop yields. In course of time, plants have evolved complex mechanisms to regulate the uptake, mobilization and intracellular concentration of metal ions to alleviate the stress damages. Since, the functional translated portion of the genome plays an essential role in plant stress response, proteomic studies provide us a finer picture of protein networks and metabolic pathways primarily involved in cellular detoxification and tolerance mechanism. In the present review, an attempt is made to present the state of the art of recent development in proteomic techniques and significant contributions made so far for better understanding the complex mechanism of plant metal stress acclimation. Role of metal stress related proteins involved in antioxidant defense system and primary metabolism is critically reviewed to get a bird’s-eye view on the different strategies of plants to detoxify heavy metals. In addition to the advantages and disadvantages of different proteomic methodologies, future applications of proteome study of subcellular organelles are also discussed to get the new insights into the plant cell response to heavy metals.